TI_GERICHTE 52.2017.596 vom 18. Oktober 2017 , Nuovo accertamento del limite forestale a contatto con la zona edificabile - TI Tribunale d'appello (2017)
Nuovo accertamento del limite forestale a contatto con la zona edificabile